Barley genotype influences stabilization of rhizodeposition-derived C and soil organic matter mineralization. (April 2016) - Mwafulirwa, Lumbani; Baggs, Elizabeth M.; Russell, Joanne; George, Timothy; Morley, Nicholas; Sim, Allan; de la Fuente Cantó, Carla; Paterson, Eric
Abstract: Rhizodeposition is an important source of substrate for microbial communities, supporting activities including soil organic matter (SOM) and nutrient cycling. Therefore, it is a potential trait of interest for crop plants, particularly in the context of variety selection for sustainable production systems. However, we do not have a good understanding of (i) whether there is significant variation in root-C deposition between varieties of important agricultural crops and (ii) whether variation in C deposition between varieties leads to major differences in C cycling in soil. In two experiments, we assessed variations in C deposition amongst barley genotypes and their respective impacts on microbial activity and SOM dynamics. In experiment 1, we applied 13 C–CO2 labelling to selected barley recombinant chromosome substitution lines (RCSLs) and traced root-derived C in surface soil CO2 efflux, soil microbial biomass-C (MBC), soil solution, and soil particle-size fractions. In experiment 2, we conducted MicroResp analysis using 15 ecologically relevant C substrates to assess the impacts of barley genotypes on microbial activity. Soil respiration measurements (partitioned into plant- and SOM-derived components) revealed genotype-specific effects on plant-derived C, SOM-derived C and total C respired as CO2 . For particle-size fractionation, we found that incorporation of plant-derived C to the silt-and-clay fraction varied between genotypes, indicating differences in relative stabilization of root-derived C as a result of barley genotype. Our data did not indicate genotype effects on total MBC size or dissolved organic-C (DOC) in soil solutions, but significant differences in plant-derived MBC and DOC were observed. MicroResp analysis showed differential utilization of 7 substrates (glucose, trehalose, lignin, arabinose, alanine, aminobutyric acid and lysine) revealing variation in community level physiological profiles (CLPPs) of soil microbes as impacted by barley genotypes. Furthermore, we found significant clustering of microbial CLPPs as a function of RCSLs and parent lines (Caesarea 26-24 and Harrington) suggesting a strong plant genetic control of the barley microbiome, and that this genetic control is heritable. Our results demonstrate barley genotype-specific effects on soil processes, revealing the potential for germplasm selection and variety improvement in barley to support sustainable production systems. Highlights: We applied 13 C–CO2 labelling to barley plants and traced the fates of root-derived C. Plant- and SOM-derived surface soil CO2 –C fluxes varied between genotypes. Incorporation of plant-derived C to the fine soil fraction varied between genotypes. Soil microbial community physiological profiles clustered as a function of genotypes.